3-[5-(1H-Indol-3-ylmethylene)-4-oxo-2-thioxothiazolidin-3-yl]-propionic Acid as a Potential Polypharmacological Agent - Yulian Konechnyi; Andrii Lozynskyi; Iryna Ivasechko; Tetiana Dumych; Solomiya Paryzhak; Oksana Hrushka; Ulyana Partyka; Iryna Pasichnyuk; Dmytro Khylyuk; Roman Lesyk (MDPI AG, 2023)
Searching for new types of biological activities among preliminarily identified hit compounds is a key challenge in modern medicinal chemistry. In our study, a previously studied 3-[5-(1H-indol-3-ylmethylene)-4-oxo-2-thioxothiazolidin-3-yl]-propionic acid (Les-6614) was screened for antimicrobial, antifungal, anti-allergic, and antitumor activities. Moreover, cytotoxicity, molecular docking, and SwissAdme online target screening were accomplished. It was determined that the Les-6614 has slight antimicrobial and antitumor activity. However, the studied compound decreased IgE levels in sensitized guinea pigs by 33-86% and reduced IgA, IgM, IL-2, and TNF-α, indicating anti-inflammatory and anti-allergic aactivities. According to the SwissADME web tool, target predictions for Les-6614 potentially have an affinity for lysosomal protective protein, Thromboxane-A synthase, and PPARγ. The molecular docking confirmed that the studied 2-thioxo-4-thiazolidinone derivative showed good bonding with LLP and TXAS, leading to stable protein-ligand complexes. Additionally, Les-6614 is a potential PPARγ modulator, which is important in the pathogenesis of allergy, cancer, and cardiovascular diseases.